Role of early catheter-based interventions in acute pulmonary embolism: a case report - Nirmal, Jasmine; Pal Singh Kaler, Gajinder; Singh Dua, Kanwal Preet (International Journal of Research in Medical Sciences, 2025)
Acute pulmonary embolism (PE) is a life-threatening condition requiring prompt and effective treatment. We present an interesting case of Intermediate-high-risk PE patient who underwent catheter-directed thrombolysis with thrombosuction cum thrombectomy, resulting in significant clinical improvement. The patient had evidence of deep vein thrombosis and presented with dyspnoea and hypotension. Following CT pulmonary angiography confirmation, he underwent catheter-directed interventions using a penumbra CAT 6 catheter (Continuous Aspiration Mechanical Thrombectomy Catheter) along with receiving very low-dose thrombolytic therapy (Alteplase 20 mg). Post-procedure, the patient showed marked improvement, with no major complications. He was discharged on Rivaroxaban and remained asymptomatic on follow-up. This case demonstrates the effectiveness, early recovery and safety of catheter-directed interventions in managing acute PE, highlighting their potential as valuable treatment options for selected patients.